Clinical outcomes after trans‐catheter aortic valve replacement in men and women in Ontario, Canada. Issue 3 (1st February 2017) - Czarnecki, Andrew; Qiu, Feng; Koh, Maria; Prasad, Treesa J.; Cantor, Warren J.; Cheema, Asim N.; Chu, Michael W.A.; Feindel, Christopher; Fremes, Stephen E.; Kingsbury, Kori; Natarajan, Madhu K.; Peterson, Mark D.; et al.
Abstract : Objective: Our objective was to evaluate sex‐differences in outcomes after trans‐catheter aortic valve replacement (TAVR) in a population‐based cohort from Ontario, Canada. Background: Prior studies comparing outcomes in men and women after TAVR have yielded divergent results. Some studies have suggested that women have better survival than men while others have not corroborated this finding. Methods: A retrospective observational cohort study was conducted using chart abstraction data on all TAVR procedures performed between 2007 and 2013 in Ontario, Canada. Patients who had emergency TAVR procedures were excluded. The primary outcome was all‐cause mortality at 30‐days and 1‐year. Secondary outcomes included mortality at last follow‐up, cause‐specific, and all‐cause hospital readmission. Inverse probability of treatment weighting (IPTW) using propensity score was used to adjust for baseline differences between men and women. Results: The final study cohort consisted of 453 women and 546 men with a mean follow‐up of 3.5 years. Women were generally older and more frail but had less comorbid conditions. Women had lower unadjusted mean EuroScores (7% ± 5% vs 8% ± 7%; P  = 0.008), but underwent significantly more trans‐apical procedures (26.5% vs 19.2%; P  = 0.006) than men. After IPTW, the groups were well balanced. Although mortality was numerically higher for women at 30‐days (7.2% vs 5.4%), this was not statistically significant ( P  = 0.34). At 1‐year, there was no difference in mortality (18.2% vs 19.2%; P  = 0.85). There were no significant differences in all‐cause readmission. Conclusion: In this population‐based cohort including all patients undergoing TAVR, mortality or all‐cause readmission were not significantly different between men and women. © 2017 Wiley Periodicals, Inc.